Elasticcluster: explorando a ociosidade de clusters virtuais para execução de aplicações do tipo saco de tarefas - Braga, Antonio Rafael (2012)
In cloud computing, elasticity and capacity of load isolation allow their resources to be provisioned and released in response to dynamic workloads with reduced downtime. These characteristics are typical of clusters hosted in a cloud (virtual cluster - VC), so that these resources need to be managed in order to minimize its waste in cloud providers and ensure that resource performance is not adversely affected. This work proposes a policy for dynamic adaptation of virtual clusters (VCs) to reduce the number of idle resources without compromising their performance of resources. The proposed algorithm, based on heuristics, performs instantiation/shut-down of the virtual machines (VMs) in virtual clusters according variation in demand for resources of applications of type Bag-of-Tasks, BoT. The algorithm has been specified, verified and validated using Petri Nets formalism. The selected metrics to evaluate the proposal performance in three different scenarios are the total amount of machine started, amount of idle machines reused, total time of execution the application and average number of clusters started. The results showed that the adaptation policy proposal is able to reduce idle and the overhead of a virtual cluster and thus improve power consumption.